INNV-14. ADJUVANT CHEMOTHERAPY AFTER SEVERE MYELOTOXICITY DURING TEMOZOLOMIDE CHEMORADIATION IN GLIOMAS. IT IS FEASIBILE?. (11th November 2019) - Villani, Veronica; Fabi, Alessandra; Gaviani, Paola; Rudà, Roberta; Lombardi, Giuseppe; Simonetti, Giorgia; Silvani, Antonio; Pronello, Edoardo; Minniti, Giuseppe; Pace, Andrea
Abstract: INTRODUCTION: Malignant gliomas are aggressive primitive brain tumor in adults. Today, the standard of care is Temozolomide (TMZ) administered daily with radiation therapy, followed by adjuvant TMZ. TMZ treatment has been considered to have a low toxicity profile. However, during concomitant treatment some patient may develop a severe myelosuppression. This toxicity may be in some cases prolonged and lead to treatment discontinuation. METHODS: We have retrospectively collected data from 5 Italian neuro-oncological centers, about glioma patients who developed severe and prolonged hematological toxicity during concomitant chemoradiotherapy with TMZ. The purpose of this study is to evaluate: percentage of patients receiving adjuvant chemotherapy after severe myelotoxicity; rate of toxicity observed during adjuvant chemotherapy. RESULTS: 54 glioma patients who developed myelosuppression of grade 3 or 4 were considered. Histology was Glioblastoma in 45 patients (83%); 63% of patients were female. Myelotoxicity during concomitant phase occurred at a median of 4 weeks (range 1–8) from the start of treatment. After recovery of myelotoxicity 19 patients did not received any treatment while 35 (65%) were treated with chemotherapy (28 received standard TMZ, one TMZ with metronomic schedule, 2 lomustine and 4 other agents). Among patients treated with TMZ, 13 patients presented hematological toxicity grade 3–4 which required treatment discontinuation in 7 cases (20%). CONCLUSION: the results of our study show that 80% of glioma patients presenting severe myelotoxicity during concomitant radiochemotherapy may be treated with maintenance TMZ after recovery of myelosuppression.